# `2x + 6y + 3 > 0` Determine whether (0, 0) satisfies each inequality.

*print*Print*list*Cite

### 2 Answers

The first step in determining the answer to this equation, is to substitute (0,0) into the equation.

x=0 and y=0

So, 2x+6y+3>0

Becomes 2(0) +6(0) +3>0

0 +0 +3>0

3>0

3 is greater than 0; therefore, (0,0) is a correct solution for this equation.

Given

`2x+6y+3>0` ; (x,y)= (0,0)

to find whether (0,0) satisfies the inequality or not

sol:

By substituting (0,0) we will get to know whether it satisfies the inequality.

`2x+6y+3>0` ; (0,0)

=> 0+0+3>0

=> 3>0 :** True**

**So , (0,0) satisfies the inequality **`2x+6y+3>0`